E-COMMERCE DAN SISTEM INFORMASI AKUNTANSI SEBAGAI FAKTOR PENDORONG PENGAMBILAN KEPUTUSAN MAHASISWA AKUNTANSI UNTUK BERWIRAUSAHA - Herlina Pusparini; Nurabiah Nurabiah; Yusli Mariadi (Jurnal Aplikasi Akuntansi, 2021)
The purpose of this study was to analyze the effect of e-commerce and the use of accounting information systems in making entrepreneurial decisions. This study used the Technology Acceptance Model (TAM) and contingency theory where this theory will be able to explain the acceptance of a technology and the relationship between the application of the used of accounting information systems and e-commerce to influence the behavior of students majoring in Accounting in entrepreneurship. The population in this study were active accounting undergraduate students who have taken entrepreneurship courses and accounting information systems for PTN and PTS in the city of Mataram. The sampling technique used purposive sampling method, data were collected by 142 distributed questionnaires. Data analysis techniques used the PLS 3.0 smart application.The results of the study indicate that the e-commerce has a positive and insignificant effect on decision making of accounting students in entrepreneurship and the accounting information system has a significant positive effect on decision making of accounting students in entrepreneurship.